miR-494 Contributes to Estrogen Protection of Cardiomyocytes Against Oxidative Stress via Targeting (NF-κB) Repressing Factor - Tang, Zhi-Ping; Zhao, Wei; Du, Jian-kui; Ni, Xin; Zhu, Xiao-Yan; Lu, Jian-Qiang (Frontiers in Endocrinology, 2018)
Oxidative stress plays a pivotal role in the initiation and progression of cardiac diseases. Estrogens have been demonstrated to exert pleiotropic cardioprotective effects, among which antioxidative stress is one of the key effects linking estrogens to cardioprotection. By using a microRNAs (miRs) microarray screening approach, we discovered an increase in miR-494, which is known to exert cardioprotective effects, in estrogen-treated cardiomyocytes. We hypothesized that the upregulation of miR-494 might contribute to estrogen-mediated cardioprotection against oxidative stress. We found that E2 stimulates miR-494 expression via ERα in both cardiomyocytes and the myocardium of female mice. The miR-494 inhibitor attenuated the protective effect of 17β-estradiol (E2) against oxidative stress-induced injury in cardiomyocytes. By contrast, the miR-494 mimic protected cardiomyocytes against oxidative stress-induced cardiomyocyte injury. Using real-time PCR, western blot and dual-luciferase reporter gene analyses, we identified nuclear factor kappa B (NF-κB) repressing factor (NKRF) as the miR-494 target in cardiomyocytes. E2 was found to inhibit NKRF, thus activating NF-κB through a miR-494-dependent mechanism. In addition, the protective effects of E2 and miR-494 against oxidative stress in cardiomyocytes were eliminated by the NF-κB inhibitor. In summary, this study demonstrates for the first time that estrogen inhibits NKRF expression through ERα-mediated upregulation of miR-494 in cardiomyocytes, leading to the activation of NF-κB, which in turn results in an increase in antioxidative defense. ERα-mediated upregulation of miR-494 may contribute to estrogen protection of cardiomyocytes against oxidative stress.